Influência dos contornos de grãos nas propriedades elétricas de hematita policristalina modificada com diferentes elementos químicos - Destro, Fabrício Benedito (2020)
The use of molecular hydrogen produced by photoelectrochemical cells is an alternative to fossil fuels, economically and environmentally. Hematite (α-Fe2O3) is a promising candidate to the realization of photoelectrochemical water splitting, by having low bandgap, chemical stability and low cost. However, disadvantages as low electrical conductivity and low lifetime of photogenerated holes harm its theoretical efficiency. Literature has emphasized the production of nanostructured and/or modified hematite photoelectrodes aiming to get around such negatives, but due to the great number of interfaces present in the system, there is not a quali or quantitative control in the contribution of each one on the efficiency loss. Therefore, is proposed a study with a simplified model, using a polycrystalline ceramic body modified with many cations (Sn, B, Ti, Zn, Zr and Sb), sintered at two temperatures, to verify the effect of grain boundaries, besides the different kinds of modifiers, on the electrical properties of hematite. The samples produced showed high relative density, besides different electric behaviors due to the different defects formed by the insertion of modifiers. In the case of modifications with Sn, it was formulated the hypothesis of the separation in two distinct grain boundary populations, as the sintering temperature gets larger. One of the components have a larger relaxation time, which translates into a larger electrical resistance. Ti and Zr present similar behaviors as Sn. B did not present any enhancement, probably because its valence remains the same as iron. Zn, however, induced the formation of a secondary dielectric phase. Sb was appropriated to enhance hematite’s electrical conductivity, although the presence of a secondary phase limits its application. However, the system also presented a grain bounday component with high relaxation time, acting as a limiter of the conductivity.